Automatic control, mechatronics and industrial engineering : proceedings of the International Conference on Automatic Control, Mechatronics and Industrial Engineering (ACMIE 2018), October 29-31, 2018, Suzhou, China - International Conference on Automatic Control, Mechatronics and Industrial Engineering (2018 : Suzhou, China).; He, Yigang; Qing, Xue (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
Engineering technology development and implementation play an important role in making the industry more sustainable in an increasingly competitive world. This book covers significant recent developments in both fundamental and applied research inthe engineering field. Domains of application include, but are not limited to, Intelligent Control Systems and Optimization, Signal Processing, Sensors, Systems Modeling and Control, Robotics and Automation, Industrial and Electric Engineering, Production and Management. This book is an excellent reference work togetup to date with the latest research and developments in the fields of Automation, Mechatronics and Industrial Engineering. It aims to provide a platform for researchers and professionals in all relevant fields to gain new ideas and establish great achievements in scientific development.
"A Balkema book."
OCLC-licensed vendor bibliographic record.
Keywords: Automatic control -- Congresses; Mechatronics -- Congresses; Industrial engineering -- Congresses; TECHNOLOGY & ENGINEERING / Engineering (General); SCIENCE / Mechanics / General; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General